Simulium (Gomphostilbia) lemborense, a new black fly species (Diptera: Simuliidae) from Flores, Indonesia - Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Chen, Chee Dhang; Lau, Koon Weng; Halim, Muhammad Rasul Abdullah; Low, van Lun; Ya’cob, Zubaidah; Abdullah, Nurul Ashikin; Suana, I. Wayan (Zootaxa, 2017)
Simulium (Gomphostilbia) lemborense sp. nov. is described based on adults, pupae and mature larvae from Flores, in the eastern part of the Sunda Archipelago, Indonesia. This new species is placed in the Simulium batoense species-group of the subgenus Gomphostilbia Enderlein, representing the most eastern distribution record for the group. This new species is characterized by a narrow female frons and pupal gill with eight filaments, of which two filaments of the ventral pair are three to four times as long as the six other filaments. Taxonomic notes are provided to distinguish this new species from related species.